Analysis of criticality level of mangrove land in Rawa Aopa Watumohai National Park, Southeast Sulawesi Province - Agusrinal, Agusrinal (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2023)
As part of the life support system, the mangrove ecosystem in the Rawa Aopa Watumohai National Park (TNRAW) has an ecological function as a spawning ground for fish in the waters, a filter for sea water intrusion into the mainland, and an absorber of heavy metals that are harmful to life, habitat for wildlife. migratory bird shelters; as well as barrier to coastal abrasion, hurricane winds and tsunamis. Aim of this study were to determine the critical level of mangroves using the terrestrial method (field survey) and to formulate the factors causing the criticality of mangroves in TNRAW. This research uses  vegetation and descriptive analysis. The results of this study indicate that there are four families and eight species of mangroves in the research location. The four families are Meliaceae, Rhizophoraceae, Avicenniaceae and Combretacea with the dominating family was Rhizophoracea. Mangroves species found were Xylocarpus granatum K., Bruguiera gymnorrhiza L., Rhizophora mucronata Bl., Rhizophora apiculata L., Ceriops decandra, Ceriops tagal, Avicennia alba and Lumnitzera racemosa.  The highest and lowest mangrove species diversity indexes in TNRAW were the seedling and tree strata, respectively with values 1,733 and 1,570. For the critical level of mangrove land measured at the four research stations, it shows that the mangrove ecosystem at the four research station is in a damaged condition. Causal factors of mangrove land critical in TNRAW were economic factors, education and skills, and weak of supervision of the authorities.